2018
DOI: 10.1016/j.jana.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

“You are always hiding. It's the worst way to live.” Exploring Stigma in African Immigrants Living With HIV in a Large Northwest U.S. Metropolitan Area

Abstract: African immigrants living in the United States are disproportionately and uniquely affected by HIV. Evidence shows that stigma may contribute to this inequity. Applying a biopsychosocial model of health, our qualitative study explored HIV-related stigma and its impact on African immigrants living with HIV in a large northwestern U.S. metropolitan area. We conducted in-depth, semi-structured interviews with 20 African immigrants living with HIV. In the biological health realm, HIV-related stigma contributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
3
12
0
3
Order By: Relevance
“…Our patient explained that she didn’t know how others would react to her diagnosis. Other studies have shown similar findings in which participants indicated that they felt shunned, out of place, and judged [17, 19, 20]. This leads to multiple other mental health and disease-related issues.…”
Section: Discussionsupporting
confidence: 52%
“…Our patient explained that she didn’t know how others would react to her diagnosis. Other studies have shown similar findings in which participants indicated that they felt shunned, out of place, and judged [17, 19, 20]. This leads to multiple other mental health and disease-related issues.…”
Section: Discussionsupporting
confidence: 52%
“…We observed consistency in descriptions of stigma among participants from different regions of Africa and who entered HIV care at different time points over the past two decades. Many previous investigations have documented high levels of HIV-related stigma in the African immigrant community, [20][21][22][23] potentially driven by lower levels of both HIV knowledge and lower levels of risk perception compared to US-born persons. 8,21,24 Undocumented immigrants, who have less access to preventive health services and lower levels of educational attainment than persons with legal immigration status, 25,26 may depend to a higher degree on informal social support networks where HIV-related stigma is high.…”
Section: Discussionmentioning
confidence: 99%
“…21 Other studies of African immigrants at risk for or living with HIV have only peripherally examined the role of immigration status. 8,14,22,23,30,31 By exploring the fears, uncertainties, and structural factors undocumented African immigrants experience surrounding HIV testing and linkage to care, particularly as these relate to their immigration status and social networks, our study provides important insights into barriers to engagement in the earliest steps in the HIV care continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Our qualitative results highlight stigma and misinformation as critical barriers that limit HIV test uptake among African-born individuals. HIV-related stigma is common among African-born communities in high income countries and has been previously identified as a factor that hinders HIV testing and disclosure in this community [3337]. While only two people mentioned confidentiality as a reason for declining testing during the health fairs, it is possible that people who fear HIV testing were less likely to attend the health fairs or participate in the study.…”
Section: Discussionmentioning
confidence: 99%